2016
DOI: 10.1186/s13148-016-0205-6
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic modifier JMJD6 is amplified in mammary tumors and cooperates with c-Myc to enhance cellular transformation, tumor progression, and metastasis

Abstract: BackgroundOncogene overexpression in primary cells often triggers the induction of a cellular safeguard response promoting senescence or apoptosis. Secondary cooperating genetic events are generally required for oncogene-induced tumorigenesis to overcome these biologic obstacles. We employed comparative genomic hybridization for eight genetically engineered mouse models of mammary cancer to identify loci that might harbor genes that enhance oncogene-induced tumorigenesis.ResultsUnlike many other mammary tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 69 publications
0
66
0
Order By: Relevance
“…Indeed, JMJD6 has been found to be highly expressed in clinical ERα-positive breast tumor samples (Aprelikova et al, 2016, Lee et al, 2012, Poulard et al, 2015). JMJD6 has been shown to possess, at least two types of enzymatic activities, demethylation (Liu et al, 2013, Chang et al, 2007) and hydroxylation (Webby et al, 2009), which are important for its function in gene transcription and splicing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, JMJD6 has been found to be highly expressed in clinical ERα-positive breast tumor samples (Aprelikova et al, 2016, Lee et al, 2012, Poulard et al, 2015). JMJD6 has been shown to possess, at least two types of enzymatic activities, demethylation (Liu et al, 2013, Chang et al, 2007) and hydroxylation (Webby et al, 2009), which are important for its function in gene transcription and splicing.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its function in transcriptional control, we and others have shown that JMJD6 also interacts with multiple splicing factors, and is involved in gene splicing control (Heim et al, 2014, Webby et al, Liu et al, 2013, Rahman et al, 2011, Yi et al, 2017). JMJD6 has been implicated in a multitude of biological processes, including embryonic development (Bose et al, 2004, Li et al, 2003, Kunisaki et al, 2004), cell cycle control (Wang et al, 2014a), cellular proliferation and motility (Lee et al, 2012, Chen et al, 2014), adipocyte differentiation (Hu et al, 2015) and development of various types of cancers, such as breast (Poulard et al, 2015, Lee et al, 2012, Aprelikova et al, 2016), lung (Zhang et al, 2013) and colon cancer (Wang et al, 2014a). …”
Section: Introductionmentioning
confidence: 99%
“…JMJD6 could demethylate the histone arginine marks . Moreover, studies showed that the JMJD6 demethylase enzyme dimethylated histone 3 at arginine 2 (H3R2me2s), and histone 4 at arginine 3 (H3R2me2s) . JMJD6 expression significantly increased in PE .…”
Section: Epigenetic Changes In Pementioning
confidence: 99%
“…Furthermore, p19ARF binds with Myc and prevents Myc‐mediated tumorigenesis in a p53‐independent manner . JMJD6 cooperates with Myc to enhance tumorigenesis through suppressing Myc‐induced apoptosis . JMJD6 binds to the p19ARF promoter and demethylates Arg3 of histone H4, thereby repressing p19ARF and reducing p53 levels.…”
Section: Mechanisms Of Jmjd6 In Promoting Cancer Developmentmentioning
confidence: 99%
“…12 In both ER+ and ER− breast cancer patients, elevated expression of JMJD6 is positively associated with histological grade, age, lymph node metastasis, tumour size and advanced tumour node metastasis (TNM). 12,62 Unfavourable survival was observed in high JMJD6 expressers with ER+ breast cancer. 10,62 However, in ER− breast cancer patients, several studies have reported that there is no significant correlation between JMJD6 level and survival, probably due to the high level of JMJD6 expression in ER− breast cancer.…”
Section: Breast Cancermentioning
confidence: 99%